How far the demographic profile of oil and gas workes influences effectiveness of NIOSH safety passport / Nur Amalina Ab Hamid - Ab Hamid, Nur Amalina (2010)
The main purpose of this research is to how far the demographic profile of oil and gas contractor influences the effectiveness of NIOSH Safety Passport toward contractor oil and gas industry at Melaka. As information, NIOSH Safety Passport is a safety program that develops by NIOSH to provide the guidance to contractor especially for oil and gas industry and it also part of the risk control which is under administration control. Besides others factors, researcher like to study on the demographic profile because it have the concept of human being where the demographic such as age, gender, education, position and working experience is the first factor will influence thinking of human especially when they need to make decision. The main objective of this study is to identify the level of effectiveness of NIOSH Safety Passport. Otherwise, the objective of this research is to identify whether participant especially contractor worker agree with the effectiveness of NIOSH Safety Passport and which of demographics profile contribute to the effectiveness of NIOSH Safety Passport. This study was using sample size of 170 respondents at oil and gas industry. The findings are interpreted using Statistical Package for Social Science (SPSS) program to analyze the data. In order to test the effectiveness, researcher use mean as the factor to see the level of the effectiveness of NIOSH Safety Passport and t-test to see the significant of relationship.